Experience with Minimally Invasive Ponto Surgery and Linear Incision Approach for Pediatric and Adult Bone Anchored Hearing Implants. (April 2020) - Bezdjian, Aren; Smith, Rachel Ann; Gabra, Nathalie; Yang, Luhe; Bianchi, Marco; Daniel, Sam J.
Purpose: To compare intra- and postoperative outcomes between the standard linear incision with tissue preservation and the Minimally Invasive Ponto Surgery (MIPS). Study Design: A non-randomized retrospective cohort series. Methods: Medical files were reviewed of adult and pediatric bone anchored hearing implant recipients. Extracted outcomes included patient characteristics, implant survival, operative time, anesthesia use, intra and postoperative complications, soft tissue tolerability assessed by the Holger's classification, and implant stability assessed by the Resonance Frequency Analysis (RFA). Outcomes were compared between two surgeries. Results: A total of 59 implants were placed (21 MIPS; 38 linear). Conductive hearing loss was the most common etiology for implantation. Surgery was conducted under local anesthesia in 67% of MIPS patients and 16% of linear patients. No intraoperative complications were reported for both surgical approaches and no implants were lost. Patients undergoing implantation via the MIPS approach displayed less skin reaction postoperatively, however this was not significant ( P = .2848). The most common Holgers score for both groups was grade 1. The median and mean surgical duration for the MIPS group was statistically lower than the linear group ( P = .0001). Implant stability measured by the RFA implant stability quotient was greater in the MIPS cohort. Conclusion: The MIPS approach seems either similar or superior to the linear approach in all perioperative outcomes evaluated. Outcomes such as surgical duration, anesthesia choice and implant stability measurements support implantation through the MIPS approach for patients meeting eligibility criteria.